1996
DOI: 10.1172/jci119095
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide may mediate the hemodynamic effects of recombinant growth hormone in patients with acquired growth hormone deficiency. A double-blind, placebo-controlled study.

Abstract: We studied the effects of recombinant growth hormone on systemic nitric oxide (NO) formation and hemodynamics in a double-blind, placebo-controlled trial in adult patients with acquired growth hormone deficiency. 30 patients were randomly allocated to either recombinant human growth hormone (r-hGH; 2.0 IU/d) or placebo for 12 mo. In the subsequent 12 mo, the study was continued with both groups of patients receiving r-hGH.In months 1, 3, 6, 9, and 12 of each year, urine and plasma samples were collected for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
156
7
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 256 publications
(178 citation statements)
references
References 58 publications
14
156
7
1
Order By: Relevance
“…In contrast to the findings described above, both in vitro [26] and in vivo studies [27,28] indicate that GH induces eNOSmediated NO production. In the human endothelial cell line, EAht926, high concentrations of GH regulate eNOS expression and NO production [26] , effects that also occur in human aortic endothelial cells [29] .…”
Section: Introductioncontrasting
confidence: 83%
See 1 more Smart Citation
“…In contrast to the findings described above, both in vitro [26] and in vivo studies [27,28] indicate that GH induces eNOSmediated NO production. In the human endothelial cell line, EAht926, high concentrations of GH regulate eNOS expression and NO production [26] , effects that also occur in human aortic endothelial cells [29] .…”
Section: Introductioncontrasting
confidence: 83%
“…In the human endothelial cell line, EAht926, high concentrations of GH regulate eNOS expression and NO production [26] , effects that also occur in human aortic endothelial cells [29] . Based on these findings, the loss of GH in humans decreases both blood flow and NO levels, whereas GH replacement restores these vascular responses [27,30,31] , indicating that patients with GH deficiency are at increased cardiovascular risk [32] .…”
Section: Introductionmentioning
confidence: 96%
“…This variant has been shown to be associated with decreased IGF-1 concentrations, and IGF-1 has been shown to stimulate endothelial nitric oxide formation. 18 Such observations might explain the association of rs34911341 with hypertension. 11 In single-locus analysis, no other studied SNP was associated with hypertension or blood pressure.…”
Section: Discussionmentioning
confidence: 97%
“…These patients demonstrate normal blood pressure, hypotension or hypertension (for review see (2)). They also have endothelial dysfunction (3) and decreased nitric oxide (NO) formation (4). Several studies have shown the clinical benefits of GH therapy on cardiovascular function in these patients, such as unchanged or decreased systolic and diastolic blood pressure (BP), increased cardiac output (CO), increased heart rate (HR) (4,5), increased NO formation (4) and decreased vascular resistance (5).…”
Section: Introductionmentioning
confidence: 99%